Audit Kualitas Perangkat Lunak pada Sistem Informasi Inventori Berbasis Web: Studi Kasus Repositori Open Source Menggunakan Standar ISO/IEC 29119 - Resnawati Kusnandar; Muhamad Yusup; Chairul Anwar (PT Jurnal Cendekia Indonesia, 2025)
The reuse of open-source code from public repositories like GitHub to accelerate business information system development often neglects quality assurance aspects. This practice poses high risks as raw code may contain hidden defects that jeopardize data integrity. This study aims to conduct an independent quality audit on the